Wages, Employment and Incentives in the Public Sector in Hungary - Gabor Kezdi (Hungarian Academy of Sciences, Institute of Economics, Labour Research Department, 1998)
The paper analyzes the changes in the relative labor market position of the public sector employees, using both macro-level employment statistics and large wage surveys. While competitive employment decreased by more than 30 per cent during the transition, number of public employees have not change a lot, so a very large public employment ratio was reached in 1995. Due to obvious budget reasons, these trends led to dramatic decreases in relative public sector salaries, within comparable groups. For some occupation groups, unmeasured but not illegal differences can compensate for earnings losses, but the ratio of these employees does not seem to be significant. The widening of private-public salary gap could have than two major effects: increasing ratio of less qualified employees in public institutions and/or major role of illegal benefits in workers' compensation. As none of these results are favorable from social perspective, public sector reform should consider significant changes in public employment incentives.
Keywords: 330